Mass mortality of the invasive echinoid Diadema setosum (Leske, 1778) in Crete, East Mediterranean Sea - SKOURADAKIS, GRIGORIOS; VERNADOU, EMMANOUELA; KOULOURI, PANAYOTA; DAILIANIS, THANOS (Mediterranean Marine Science, 2024)
Diadema setosum is an echinoid of Indo-Pacific origin that invaded the Mediterranean Sea in 2006. It is an ecosystem engineer with an important ecological function in its native range, but it can have a detrimental effect on Mediterranean reefs. Recently in 2022 a mass mortality event (MME) affecting this species was recorded in the east Aegean Sea in the eastern part of the Mediterranean basin. We are reporting herein a westward progression of the MME in 2023 affecting established populations in various locations around the island of Crete.